1-[5-Acetyl-4-(4-bromophenyl)-2,6-dimethyl-1,4-dihydropyridin-3-yl]eth anone monohydrate - Reddy, P.B.; Vijayakumar, V.; Sarveswari, S.; Narasimhamurthy, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The 1,4-dihydropyridine ring in the title hydrate, C17H18BrNO2 center dot H2O, has a flattened-boat conformation, and the benzene ring is occupies a position orthogonal to this [dihedral angle: 82.19 (16)degrees]. In the crystal packing, supramolecular arrays mediated by N-H center dot center dot center dot O-water and O-water-H center dot center dot center dot O-carbonyl hydrogen bonding are formed in the bc plane. A highly disordered solvent molecule is present within a molecular cavity defined by the organic and water molecules. Its contribution to the electron density was removed from the observed data in the final cycles of refinement and the formula, molecular weight and density are given without taking into account the contribution of the solvent molecule.